A comparative study of cold atmospheric plasma treatment, chemical versus physical strategy. (17th December 2020) - Wang, Qihui; Malyavko, Alisa; Yan, Dayun; Lamanna, Olivia K; Hsieh, Michael H; Sherman, Jonathan H; Keidar, Michael
Abstract: To date, reactive oxygen species and reactive nitrogen species have been regarded as the key factors causing the observable cellular death of cold atmospheric plasma (CAP)-treated cancer cells. The chemical basis of the conventional CAP treatment highlights apoptosis as the main CAP-triggered cell death mechanism. However, we recently demonstrated a strong anti-melanoma effect based on physically-based CAP treatment. In this study, we compared the anti-cancer effect of chemically-based versus physically-based CAP treatment on four typical cancer cell lines in vitro . Three of these cancer cell lines were more sensitive to the physical factors in CAP than the chemical factors in CAP, while the fourth cell line followed the original trend of being more sensitive to chemical factors. This study demonstrated that the physically-based CAP treatment could be an effective anti-cancer approach, which might have a deep impact on the future application of CAP in medicine.